Processing of data of experimental measurements of electric power quality characteristics on example of voltage deviation levels - А. V. Ded; S. P. Sikorskiy; I. B. Daniukov (Омский научный вестник)
The article shows results of processing of data about deviations of supply voltage levels in electric networks of 0,38 KV of the Omsk State Technical University, obtained within the limits of obligatory energetic examination. At given probability value for each measurement point, value of deviation of voltages of each of phases from nominal value is calculated. It has been found that the average value of deviation of the supply voltage level does not exceed for each of the phases of the values of 7 %, which is less than maximum permissible value of 10 % of set GOST.